Postoperative Use of Ketorolac Improves Pain Management and Decreases Narcotic Use Following Primary Cleft Palate Surgery. (November 2022) - Dudley, Samuel; Spence, Matthew; Frederick, Robert; Stocks, Rosemary
Objective: To study the efficacy and safety profile of ketorolac in cleft palate surgery. Design: Retrospective analysis of patients who underwent primary cleft palate surgery and received either postoperative ketorolac or opioids. Setting: Tertiary care children's hospital. Patients, Participants: Eighty-nine patients enrolled who were all younger than 36 months of age, not dependent on a gastrostomy tube, with no history of bleeding disorders, and had undergone their primary cleft palate procedure by one specific surgeon between January 2010 and June 2019. Interventions: n/a. Main Outcome Measure: Morphine equivalent dose (MED), Face, Legs, Activity, Cry, Consolability (FLACC) score, length of stay (LOS), total oral intake (mL), total oral intake/LOS, and postoperative adverse events between ketorolac and no ketorolac groups. Results: MED, FLACC score, and LOS were significantly lower in the ketorolac group compared to the no ketorolac group. One patient in the ketorolac group had a bleeding event. Conclusions: Use of ketorolac significantly decreased narcotic usage and pain scores as reported by the FLACC score. Moreover, postoperative bleeding was rare in both ketorolac and no ketorolac groups.